Developing English Reading Materials For Second Year Students Of Islamic Education In IAIH NW Anjani Especially (Islamic Education For B Class In 2018-2019) - Bisyrulhafy, Muh. (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Developing English Reading Materials for the students of IAIH NW Anjani. It modified Latief model (2009); the lecturer developed material based on data analysis taken from preliminary data. The material was validated and tried-out to B class of Islamic education in second semester 2018-2019. The result showed that this study and the product have successfully answered the students’ needs in reading skill. Therefore, the product could be used for Islamic education especially for 2rd semester.